Counselling and helping - Velleman, Richard; Aris, Sarajane; Murgatroyd, Stephen J. (Chichester, UK ; Malden, MA : BPS Blackwell, 2010)
This new edition is an indispensable introduction to the core principles of counselling for those interested in counselling and those considering training. It describes the main styles of counselling, provides an excellent framework for helping, and introduces some of the approaches and key tools used within a counselling relationship: Offers a stimulating and highly accessible introduction to the key aspects of counselling; Recurring case studies to illustrate clearly the practical application of the range of styles and approaches in counselling and experiential exercises are included in eac.
Introduction : what this book is about -- Counselling and helping -- The basic features of counselling relationships -- Being helped : creating the right conditions and expectations -- Helping the helpers -- Helping people to cope -- Helping people to do things differently -- Helping people with their thinking -- Helping people with their feelings -- Helping people with their bodies -- Helping people with their unconscious processes -- Helping people with their spirituality -- Helping people by coaching -- Helping people to use their networks -- Helping people in groups -- Summary and conclusions.
Includes bibliographical references and index.
Includes beb resources.
Print version record.
Keywords: Counseling psychology; Helping behavior; Electronic books